Risk Stratification by Coronary Perfusion Pressure in Left Ventricular Systolic Dysfunction Patients Undergoing Revascularization: A Propensity Score Matching Analysis - Hsieh, Ming-Jer; Chen, Chun-Chi; Chen, Dong-Yi; Lee, Cheng-Hung; Ho, Ming-Yun; Yeh, Jih-Kai; Huang, Yu-Chang; Lu, Yu-Ying; Chang, Chieh-Yu; Wang, Chao-Yung; Chang, Shang-Hung; Hsieh, I-Chang (Frontiers in Cardiovascular Medicine, 2022)
Background: Coronary perfusion pressure (CPP) and coronary artery stenosis are responsible for myocardial perfusion. However, how CPP-related survival outcome affects revascularization is unclear. Objective: The aim of this study is to investigate the prognostic role of CPP in left ventricular systolic dysfunction (LVSD) patients undergoing percutaneous coronary intervention (PCI) with complete revascularization (CR) or reasonable incomplete revascularization (RIR). Methods: We retrospectively screened 6076 consecutive patients in a registry. The residual SYNTAX score (rSS) was used to define CR (rSS=0) and RIR (042mmHg. Moreover, 101 pairs of RIR and CR were present in patients with CPP≤42mmHg. In patients with CPP>42mmHg, RIR was not significantly different from CR in long-term mortality [hazard ratio (HR) 1.20; 95% confidence interval (CI): 0.70–2.07; p=0.513]; However, in patients with CPP≤42mmHg, RIR had a significantly higher mortality risk than CR (HR 2.39; 95% CI: 1.27–4.50; p=0.007). Conclusions: CPP had a risk stratification role in selecting different revascularization strategies in patients with LVSD. When LVSD patients had CPP>42mmHg, RIR was equivalent to CR in survival. However, when LVSD patients had CPP≤42mmHg, RIR had a significantly higher mortality risk than CR.